A Clinico-Epidemiological Study on Peripheral Arterial Disease in Diabetes Mellitus - Dr. Amartya Kumar Misra; Dr Sudeshna Mallik; Dr Sourav Kundu, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Peripheral arterial disease (PAD) is an under-diagnosed macrovascular complication of diabetes mellitus (DM) that accelerates lower-limb morbidity and heightens cardiovascular risk. Contemporary Indian data on the clinico-epidemiological profile of PAD in DM remain scarce. Methods: We performed a cross-sectional observational study of 100 consecutive adults with established DM attending a tertiary centre in Kolkata (January–December 2023). Detailed history, examination, biochemical indices, and duplex Doppler of lower-limb arteries were recorded. PAD was graded by ankle–brachial index (ABI) and segmental stenosis (0 = normal; 4 = occlusion). Descriptive statistics, χ² tests and Pearson correlations were generated using SPSS v26; p ≤ 0.05 signified statistical significance. Results: Mean age was 55.4 ± 18.5 years; 72 % were men. Smoking (60 %), hypertension (42 %) and hyperlipidaemia (38 %) predominated. PAD symptoms lasted 4–8 weeks in 42 % of participants; intermittent claudication was most frequent (46 %), followed by ulceration (32 %) and rest pain (24 %). ABI indicated mild, moderate and severe PAD in 60 %, 32 % and 8 % respectively. Disease severity correlated strongly with diabetes duration (r = 0.85, p < 0.0001) and inversely with receipt of PAD-directed medical therapy (r = –0.47, p = 0.002). No significant association was observed for age, sex, socio-economic markers or family history. Conclusion: In this Eastern-Indian cohort, PAD occurred early (two-thirds < 60 years) and was chiefly driven by modifiable factors—smoking, hypertension, dyslipidaemia and longer diabetes duration. Routine ABI screening and aggressive risk-factor modification could curb progression to critical limb-threatening ischaemia.